PRIORITY AREAS FOR DIVERSIFICATION AND SEASONALITY OF THE TOURISM PRODUCT - Khamzaeva , Dilfuza Samarovna (Educational Research in Universal Sciences, 2023)
Seasonality provokes downtime of accommodation facilities and temporary unemployment of staff. The purpose of the study is to identify potential opportunities to smooth out the impact of seasonality on the tourism industry of the Republic of Uzbekistan. Statistical data analysis, induction and deduction were used to identify influence. An analysis of the literature on tourism research by authors from Russia, Uzbekistan and other countries was carried out. In addition, the characteristics of the seasonality factor in tourism require more detailed consideration. The article examines the importance of seasonality in the activation of tourism services in the socio-economic development of the country, the impact on the development of the tourism industry. The developed measures to smooth out the influence of seasonality can be applied not only in Uzbekistan, but also in other countries with similar characteristics of the tourism industry.